CELL MEMBRANE MEDIATED (-)-EPICATECHIN EFFECTS ON UPSTREAM ENDOTHELIAL CELL SIGNALING: EVIDENCE FOR A SURFACE RECEPTOR - Moreno-Ulloa, Aldo (2014)
The consumption of cacao-derived products, particularly in the form of dark chocolate is known to provide beneficial cardiovascular effects in normal individuals and in those with vascular dysfunction (reduced nitric oxide [NO] bioavailability and/or synthesis). Upstream mechanisms by which flavonoids exert these effects are poorly understood and may involve the participation of cell membrane receptors. We previously demonstrated that the flavanol (-)-epicatechin (EPI) stimulates NO production via Ca(+2)-independent eNOS activation/phosphorylation. We wished to investigate the plausible participation of a cell surface receptor using a novel cell-membrane impermeable EPI-Dextran conjugate (EPI-Dx). Under Ca(2+)-free conditions, human coronary artery endothelial cells (HCAEC) were treated for 10 min with EPI or EPI-Dx at equimolar concentrations (100 nM). Results demonstrate that both EPI and EPI-Dx induced the phosphorylation/activation of PI3K, PDK-1, AKT and eNOS. Interestingly, EPI-Dx effects were significantly higher in magnitude than those of EPI alone. The capacity of EPI-Dx to stimulate cell responses supports the existence of an EPI cell membrane receptor mediating eNOS activation.